Comparison of newly invented plant coagulant with commercial coagulants for treatment of latex concentrated effluent - Idris, Juferi (2007)
This study investigated the effect of coagulation process on wastewater from latex concentrate industry. The coagulation performances of dragon fruit's foliage which was a newly invented plant based coagulant and commercial coagulants such as alum, ferric chloride, polyaluminium chloride, magnesium chloride, ferrous sulfate, ferric sulfate and calcium hydroxide were studied using a jar test. The study also compared different dosages and pH values of the coagulation processes. The analysis of dragon fruit's foliage was also studied. The results revealed that the percentage removals in terms of COD, SS and turbidity of commercial coagulants (alum, ferrous sulfate, calcium hydroxide, PAC, ferric chloride and ferric sulfate) have been found to be around 97-99%, 94-97% and 99% respectively, whereas the newly invented plant-based coagulant at the same dosage of 300 - 600 mg/L demonstrates the same performances as any commercial coagulants. All the coagulants used give high percentage of BOD removal which is from 1327 mg/1 before treatment to below 100 mg/1 after treatment except for dragon fruit coagulants which gives 173.67 mg/L. However, others parameters such as sulfate, NH3-N and several heavy metals are in compliance with standard B set by Department of Environment, Malaysia. The study has proven the existence of alum compound in the dragon fruit's foliage under the XRay Diffractometer (X-RD) analysis and therefore the dragon fruit's foliage can be used as a coagulant and has a great potential as a new plant-based coagulant in latex concentrated wastewater treatment.